Non-antibiotic pharmaceutical agents as antibiotic adjuvants - Gajdács, Márió (Acta Biologica Szegediensis, 2020)
The emergence of multidrug-resistant bacteria is a global public health issue, which severely hinders clinicians in providing patients with adequate antimicrobial treatment regimens. The strategy of drug repurposing is an emerging strategy in antimicrobial chemotherapy, during which new pharmacological uses are identified for drugs already approved. The aim of our present study was to assess the adjuvant properties of several existing and widely-used pharmacological agents against bacteria in combination with reference antibiotics. Staphylococcus aureus ATCC 25923, S. epidermidis ATCC 12228, Escherichia coli ATCC 25922 and Klebsiella pneumoniae ATCC 700603 were selected for our experiments. The minimum inhibitory concentrations (MICs) of the tested compounds were determined using the broth microdilution method, while a MIC reduction assay was performed to ascertain the eﬀect of the tested compounds on the MICs of standard antibiotics (ciprofloxacin and gentamicin). Eight tested compounds (namely atorvastatin, celecoxib, clotrimazole, diclofenac-epolamine, ivermectin, lidocaine, mebendazole and terbinafine) showed antibacterial activity on the tested bacterial strains and several agents presented with various degrees of adjuvant (MIC-reducing) properties. Further experiments involving the screening of additional pharmaceutical compounds for their secondary antibacterial and adjuvant properties are warranted.